Flowsheets for hydroxyacetone–phenol binary mixture separation: The use of special distillation methods - I. S. Gaganov; E. V. Rytova; A. K. Frolkova (Тонкие химические технологии, 2023)
Objectives. To study the possibility of hydroxyacetone–phenol binary mixture (a constituent of a mixture of phenol production by the cumene method) separation in flowsheets based on the use of distillation special methods. This is the addition of separating agents to increase the relative volatility of the components of the original mixture, and the variation of pressure in the columns.Methods. A computational simulation in Aspen Plus® was used as the research method. Mathematical modeling of the vapor–liquid equilibrium was carried out using a local compositions model Non-Random Two Liquid. The viability of the latter was confirmed by comparing experimental and calculated on phase equilibrium data, and azeotropic data. The average relative error does not exceed 3%.Results. The dependence of the composition and boiling point of the hydroxyacetone–phenol azeotrope on pressure was determined in a computational experiment (as the pressure increases, the azeotrope is enriched with phenol). The possibility of using a complex of columns operating under different pressures to separate the mixture was shown (the shift of the azeotrope is about 9%). The change in the relative volatility of components of the original mixture in the presence of a high(diethylene glycol) and a low-boiling (acetone) separating agent was investigated. Both solvents are selective agents used in extractive and re-extractive distillation processes. Three technological separation flowsheets containing two distillation columns were proposed.Conclusions. The study established the operation parameters of the columns (number of theoretical stages, feed stages of the original mixture and separating agent, and reflux ratio) and energy consumption (total heat supplied to the columns boiler) of three separation flowsheets ensuring the production of products of a given quality (not less than 0.99 mol fractions). The flowsheet with diethylene glycol is characterized by the lowest energy consumption. It is recommended that complexes of extractive and re-extractive distillation be further optimized. This enables the second product of cumulus production—acetone—to be involved in the technological cycle.